Analisis Sulfur Dioksida (SO2) Udara Ambient Menggunakan Metode Pararosanilin dengan Spektrofotometer UV-Visible Kabupaten Bandung, Jawa Barat - SOFI AMALIA; IRA RYSKI WAHYUNI (Gunung Djati Conference Series, 2022)
Air pollution is the entry or inclusion of energy substances from other components into the air by human activities, so that air quality drops to a certain level which causes ambient air to not fulfill its function. This study aims to determine the concentration level of Sulfur Dioxide (SO2) in Bandung Regency. Sample measurements were carried out using a spectrophotometer based on the reference to SNI 19-719-2017 regarding the sulfur dioxide (SO2) level test using the pararosanilin method. Measurements were carried out in the range of 10.00-13.00. The concentration of sulfur dioxide in Bandung Regency is 100-200 mg/Nm3 with a threshold of 900 mg/Nm3 so it is still classified as good. This situation is caused by the presence of green trees in the district of Bandung and its surroundings. The conclusion of this study is that the concentration of SO2 at several points in Bandung Regency still meets the requirements (The requirements of ambient air quality standard of PP Number (No). 22 of 2021), so it is recommended for the government and the community to make efforts/activities to maintain healthy air quality in Bandung Regency.